6 - The Constraints of Rural Women in Informal Economic Activities in Imo State, Nigeria: https://doi.org/10.4314/ad.v34i1.57359 - Onyenechere, Emmanuella Chinenye (Africa Development, 2009)
The paper analyzes the constraints on rural women in the informal sector of Imo State, Nigeria. Lack of access roads, irregular means of transportation, inad- equate credit facilities, inaccessibility to socio-economic facilities and land ten- ure are identified as among the factors that have adverse effects on the partici- pation/activities of rural women engaged in informal economic activities in the rural areas of Imo State. The paper further reveals that a majority of rural women in Imo State, engaged in informal economic activities, do not have significant access to institutional finance, neither do they for socio-economic services that could enhance women’s informal economic activities. The paper eventually makes policy recommendations to help alleviate women’s difficulties in the informal sector.